Governance and Service Delivery: Practical Applications of Social Acco untability Across Sectors - Wetterberg, Anna; Brinkerhoff, Derick W.; Hertz, Jana C. (RTI Press, 2016)
The six case studies in Governance and Service Delivery: Practical App lications of Social Accountability Across Sectors illustrate the multi ple ways citizen participation in accountability – called social accou ntability – can lead to positive effects on governance, citizen empowe rment, and service delivery. Drawing on their extensive experience imp lementing international donor-funded programs and projects, the author s examine six recent RTI International projects in Africa and Asia. Th e analysis focuses on both intended and actual effects, and it unpacks the influence of context on implementation and outcomes achieved, as well as on prospects for sustainability. Donors, academics, policy mak ers, practitioners and others interested in sustainable development an d governance will find this systematic review invaluable.